The influence of community social capital on pre-service teachers’ career calling: the mediating role of career exploration and the moderating effect of agreeableness - Su, Xiaomin; Ahmad, Anuar; Alias, Jamsari (Frontiers in Education, 2024)
Introduction This study aims to explore the mechanism by which community social capital influences pre-service teachers’ career calling, while also examining the mediating role of career exploration and the moderating effect of agreeableness. Methods Data were collected from 455 pre-service teachers at a local undergraduate normal college in Guangdong Province, and a structural equation model was employed for analysis. Results The findings revealed a significant positive relationship between community social capital and career calling, with career exploration serving as a mediating variable between them. Additionally, agreeableness moderated the relationship between community social capital and career exploration. Discussion These results provide valuable theoretical and practical support for colleges and universities in developing community service-learning education programs that enhance pre-service teachers’ career exploration, address their individualized requirements, and cultivate their career calling.